THE INFLUENCE OF THE ROAD SURFACE ON THE TRAFFIC NOISE - Figlus, Tomasz; Wilk, Andrzej; Liscak, Stefan; Gozdek, Lukasz (Doprava a spoje, 2012)
This article deals with an issue of the road surface influence on the traffic noise. Type and structure of the surface has a great importance in terms of noise pollution in the case of dominant source of vehicles noise, which is caused with contact of tires and surface. In this article, there are the research results which aim to compare two different types of surface influencing the noise emission in the real traffic.